Urgensi Mitigasi Bencana Banjir Wilayah Kabupaten Ketapang: Kasus Studi Ruas Jalan Sei. Awan Kiri-Desa Tanjungpura - Putranto, Alan; 'Ain, Hurul; Dwi Purnomo Adwi, Teddy (Teknik Sipil, Politeknik Negeri Ketapangg, 2022)
Flood in Ketapang Regency is a hazardous environmental condition for local people. It disrupts mo-bilization and economic activities. A preliminary study was conducted to identify the causes of the flood and the solution based on engineering perspective as mitigation approach. The hydrological analysis uses 15 years of rainfall data. The maximum rainfall analysis is using Gumbel and Log Person Type III distribution. Meanwhile, the fit test's goodness uses chi-square and Smirnov-Kolmogorov method. Another anal-ysis parameter investigated is soil's physical properties, topographical conditions, and contours. It was found that the flood occurs due to: first, the inability of the soil to infiltrate water (saturated soil); second, flat contour with no significant difference in the level; third, located close to the river, which was prone to overflows during the rainy season. The solution that recommends for more cost-effective is to carry out the normalization of soil drainage channels from both sides of the road.